Controlled surface crystallization of lithium‐zinc‐alumosilicate glass‐ceramics using thermal poling. Issue 5 (4th January 2022) - Sander, Malte; Engelmann, Pawel; Jacobs, Philipp; Roos, Christian
Abstract: Two glasses from the lithium‐zinc‐alumosilicate (LZAS) glass–ceramic system were thermally poled at 0.5 and 0.9 T g and subsequently crystallized in heat‐treatment. Underneath the anode‐faced surface of the as‐poled glasses, a lithium depletion layer was found with layer thicknesses up to 15 μm. Between the depletion layer and the bulk, an accumulation of sodium was measured. Structural alterations underneath the anode‐faced and cathode‐faced surfaces of the crystallized glasses were examined using grazing‐incidence X‐ray diffraction and scanning electron microscopy. A mainly amorphous layer was observed on all anode‐faced surfaces, each containing only small amounts of high‐quartz solid solution (high‐quartz s.s.). The low crystalline content was attributed to a reduced lithium content when compared to the untreated reference. Additionally, in one sample a keatite solid solution (keatite s.s.) formed in the anode‐faced surface with its phase content increasing with the poling temperature. The transformation of high‐quartz s.s. to keatite s.s. is facilitated by a silica‐rich glass composition beneath the anode‐faced surface. Underneath the cathode‐faced surface high crystalline contents were obtained, which even exceed the crystalline phase contents found in the untreated reference samples. In combination with an observable larger lattice parameter of the high‐quartz s.s. phase, it could be assumed that Li + cations enrich at the cathode‐faced surface. The enrichment of Li + cations on the cathode‐faced and their depletion on the anode‐faced surface lead to different particle sizes. Small grains were observed underneath the amorphous layer in the anode‐faced surface, while larger grains with an overall broader particle size distribution were found on the cathode‐faced surface.